Dampak Konflik Maritim terhadap Stabilitas Keamanan Laut di Asia Tenggara - Salsabila Kamaluddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Maritime conflicts in Southeast Asia place regional stability at great challenge, especially due to the importance of these waters as international transport routes. Claims for overlapping maritime areas, illegal activities such as trespassing and unregulated copyright fishing, in particular increased geopolitical tensions in the South China Sea, have created a complex maritime security environment. These disputes not only affect state jurisdictional and maritime sovereignty, but also affect regional economic activities, including trade and marine tourism. This study uses a qualitative approach in literature research to examine the effects of these various topics on maritime stability and efforts to address legal channels and diplomatic conflicts. Using conflict theory, this study highlights the importance of regional co-operation, adherence to the International Sea Council, and the importance of adaptive security strategies as a step in mitigation. It also focuses on the relationship with maritime security with other important sectors such as logistics, energy and tourism, highlighting the need for collective action between countries in Southeast Asia.